2004
DOI: 10.1037/0021-843x.113.2.271
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2 Status and Conduct Disorder Mediate the Relationship Between Ethnicity and Alcohol Dependence in Chinese, Korean, and White American College Students.

Abstract: This study examined aldehyde dehydrogense (ALDH2) gene status, alcohol dehydrogense (ADH2) gene status, conduct disorder, and alcohol dependence in Chinese, Korean, and White American college students. Chinese had a lower rate of alcohol dependence (5%) than Koreans (13%) and Whites (17%). Koreans had a higher rate of conduct disorder (15%) than Whites (9%) and Chinese (6%). The relationship of ethnicity to alcohol dependence was mediated by ALDH2 status and conduct disorder, although Chinese ethnicity remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 47 publications
7
51
2
Order By: Relevance
“…Results are reported in Table 1. Consistent with previous studies (e.g., Luczak et al, 2004), significantly more Chinese Americans (49%) than Korean Americans (33%) carried at least one ALDH2*2 allele (χ 2 = 11.21, 1 df, p=.001). Chinese Americans were marginally more likely than Korean Americans to report that neither parent had ever used alcohol (23.3% vs 16.1% respectively; χ 2 = 3.50, 1 df, p = .061).…”
Section: Primary Comparisons Of Ethnic Groupssupporting
confidence: 78%
See 2 more Smart Citations
“…Results are reported in Table 1. Consistent with previous studies (e.g., Luczak et al, 2004), significantly more Chinese Americans (49%) than Korean Americans (33%) carried at least one ALDH2*2 allele (χ 2 = 11.21, 1 df, p=.001). Chinese Americans were marginally more likely than Korean Americans to report that neither parent had ever used alcohol (23.3% vs 16.1% respectively; χ 2 = 3.50, 1 df, p = .061).…”
Section: Primary Comparisons Of Ethnic Groupssupporting
confidence: 78%
“…The lack of association between ALDH2 status and current alcohol use or heavy episodic drinking stands in contrast to findings from previous studies linking presence of the ALDH2*2 allele to reduced rates of heavy episodic drinking (Luczak et al, 2001;Takeshita and Morimoto, 1999;Wall et al, 2001), alcohol use (Takeshita and Morimoto, 1999;) and alcohol dependence (Luczak et al, 2004;Thomasson et al, 1991). In particular, in recent studies of Asian American college students, Luczak et al (2001) and Wall et al (2001) found that ALDH2 status was associated with prior 2-week and lifetime heavy episodic drinking, respectively.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In Taiwan, the lifetime rate of AUDs was 7% (13% for men and 0.7% for women), whereas in South Korea it was 23% (43% for men and 3% for women). Consistent with these data, our laboratory found a lower rate of alcohol dependence among Chinese-American college students (5%), compared with Korean-American college students (13%) (Luczak et al, 2004).…”
supporting
confidence: 77%
“…Some East Asian ethnic groups such as Japanese and Filipino are more likely to engage in heavy drinking (9). Luczak et al (44) also reported differences in both drinking and ALDH2 *2 frequency counts between Korean and Chinese college students.…”
Section: Discussionmentioning
confidence: 95%